A scoping review protocol: Neuropsychological development in pediatric ophthalmology patients with social determinants of health analysis - Euna Cho; Justin Zhang; Rebecca Li; Sua Cho; David Kim; Emily Gorman; Moran Roni Levin; Patrice Hicks; Janet Leath Alexander (PLoS ONE, 2025)
Introduction Globally, ocular diseases have a substantial prevalence and impose a significant disease burden. Specifically, ocular diseases can negatively impact neuropsychological development for pediatric patients, including academic, social, and mental health as well as quality of life. Neuropsychological development is important, because it impacts cognitive functioning and learning, emotional and behavioral regulation, social interactions and communication, executive functions later in life, and long-term health and well-being. Detriments in neuropsychological development can be modulated by the intricate social determinants of health (SDOH) in a patient’s environment, potentially leading to exacerbated outcomes and disparities. We will conduct a scoping review with the aim of evaluating how SDOH influences the impact of ocular diseases on the neuropsychological development of pediatric patients. Methods and analysis Using a comprehensive search strategy, all relevant literature will be extracted from the following electronic databases: Cochrane Central Register of Controlled Trials (WileyOnline interface), Embase (Elsevier interface), Europe PMC, Medline (Ovid Interface), PsycInfo (EBSCO interface), and Scopus (Elsevier interface). Inclusion criteria consist of ocular disease, neuropsychiatric development, pediatric population, and social determinants of health. Covidence (Veritas Health Innovation Ltd, Melbourne, Australia) review software will be used to screen articles that meet the inclusion criteria. Extracted articles will be classified according to national income level and universal healthcare index, type of ocular disease, neuropsychological category, and social determinants of health domain. Data analysis will include a quantitative report on the percentage classification of articles by each ocular, neuropsychological, and SDOH domain category. Sub-categorization of article count by national location, income level, and presence of universal healthcare will be analyzed for each explored and observed SDOH domain.